2012
DOI: 10.1186/1471-2458-12-992
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cervical cancer incidence and mortality in Canada: national data from 1932 to 2006

Abstract: BackgroundHigh levels of participation in cervical screening are reported in Canada from the 1970’s as a result of early uptake of the Pap smear and universal Medicare. Despite recommendations to the contrary, the programs have featured early age of initiation of screening and frequent screening intervals. Other countries have achieved successful outcomes without such features. We analyzed national data to better understand mortality and incidence trends, and their relationships to screening.MethodsThe Canadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
113
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 19 publications
8
113
1
1
Order By: Relevance
“…The incidence and mortality of cervical cancer has decreased due to cytology screening in many countries (Arbyn et al, 2011;Dickinson et al, 2012). To prevent only one death from cervical cancer many screening program recommend cytology screening every year for 10 years, this is the area that many researchers want to show the importance of finding optimal intervals for screening (Kobayashi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and mortality of cervical cancer has decreased due to cytology screening in many countries (Arbyn et al, 2011;Dickinson et al, 2012). To prevent only one death from cervical cancer many screening program recommend cytology screening every year for 10 years, this is the area that many researchers want to show the importance of finding optimal intervals for screening (Kobayashi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…National media coverage emphasized Canada's role as a mid-twentieth century pioneer in cervical cancer screening and an exemplar of early detection through regular Papanicolaou (Pap) screening. Citing an 83% drop in cervical cancer deaths in Canada between 1952 and 2006 (from 13.5/100,000 to 2.2/100,000) as reported in Dickinson et al (2012), the Canadian Broadcasting Corporation noted that 'what was a rare cancer has become rarer still ' (2012). Media coverage and health education materials introducing the general public and health care providers (HCPs) to the new screening guidelines did not report the elevated risk of cervical cancer morbidity and mortality among vulnerable populations in Canada (Canadian Medical Association Journal, 2013;Cancer Care Ontario, 2012a, 2012b, leaving the impression that the picture had improved for all groups of Canadian women.…”
Section: Introductionmentioning
confidence: 99%
“…The understanding that nearly all cervical cancer is caused by oncogenic strains of the human papillomavirus (HPV) has assisted in better interpretation of the associations between behavior and cervical cancer. 8 Epidemiological studies conducted during the past 30 years have consistently indicated that cervical cancer risk is strongly influenced by measures of sexual activity, number of sexual partners, age at first sexual intercourse and sexual behavior of the women's male partners. 9 Many studies have also suggested that women with multiple sexual partners are at high risk for HPV acquisition and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%